Effectiveness of Green Mussel Shell Waste and Lime Peel as Toothpaste - Fauzy, Insan; Hasanah, Afifah Nurazizatul; Pratama, Ginanjar (Universitas Gadjah Mada, 2024)
The problem is that waste produced from green mussel shells can result in environmental pollution. Green mussel shells can be used as raw material for making toothpaste. Toothpaste is a care product that has the function of caring for healthy teeth to prevent cavities that use a combination of green mussel shells and lime peel as the main ingredients. This study aims to determine the effectiveness of toothpaste derived from green mussel shells and lime peel. This research was carried out in four stages, namely making green mussel shell flour, making lime peel extract, making toothpaste formulations and testing which included organoleptic, carbohydrate, pH, antibacterial, calcium, viscosity, centrifugation and stability testing. The design used was a Completely Randomized Design (CRD) with 5 treatment levels with different concentrations of green mussel shells, namely P1 (0), P2 (16.5%), P3 (25%), P4 (33.5%), P5 ( 50%).The research results showed that the best treatment was toothpaste with a combination of clam shell powder and lime peel extract in the P5 treatment in the antibacterial test with an inhibitory power obtained of 156.67 ± 15.28. Treatment P5 with a concentration of 50% addition of green mussel shell flour was the best treatment for toothpaste preparations.